1995
DOI: 10.1161/01.cir.91.3.821
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coronary Stenoses and Quantification of the Degree and Spatial Extent of Blood Flow Mismatch During Coronary Hyperemia With Myocardial Contrast Echocardiography

Abstract: Coronary stenoses, which are not flow limiting at rest, can be detected and the degree and spatial extent of blood flow mismatch during pharmacologically induced coronary hyperemia can be quantified with MCE using LA and RA injections of contrast. Thus, it is possible that the severity of coronary stenoses and the quantum of myocardium in jeopardy could be quantified in the future with MCE using venous injection of contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…It can also be used to assess the presence and extent of collateral perfusion during acute coronary occlusion and its impact on myocardial viability [30, 31]. MCE has also been used successfully for the detection of stable chronic coronary artery disease in the absence of prior infarction [32, 35]. …”
Section: Role Of Myocardial Contrast Echocardiography In Clinical Pramentioning
confidence: 99%
“…It can also be used to assess the presence and extent of collateral perfusion during acute coronary occlusion and its impact on myocardial viability [30, 31]. MCE has also been used successfully for the detection of stable chronic coronary artery disease in the absence of prior infarction [32, 35]. …”
Section: Role Of Myocardial Contrast Echocardiography In Clinical Pramentioning
confidence: 99%
“…Experimental studies had previously demonstrated the ability of MCE to detect coronary stenosis and to quantify the degree of MBF mismatch during pharmacological stress. [62][63][64] Studies also showed that coronary stenosis can be detected 65,66 and abnormal coronary blood flow reserve can be accurately measured 67 with MCE in humans with venous administration of microbubbles.…”
Section: Mce For Cad Detectionmentioning
confidence: 99%
“…18 During adenosine or dipyridamole vasodilation in dogs, peak MVI ratios within different myocardial regions following bolus injections of microbubbles have been shown to correlate closely with MBF ratios determined with radioactive microspheres. 19,20 When using intermittent harmonic imaging during dobutamine or adenosine stress, the peak MVI ratios (stenosed divided by normally perfused bed) correlate closely with minimal lumen diameter of the stenosed artery. 21 These animal studies led to the rst comparative studies in humans.…”
Section: Stress Echocardiographymentioning
confidence: 99%